Faktor Perilaku dalam Pemilihan Karier Auditor Internal Syariah: Framing, Groupthink, dan Penghargaan Finansial - Erika Ayu Badi’ah; Helti Nur Aisyiah (Jurnal UMKM, Manajemen dan Akuntansi, 2026)
This study examines the effect of framing, groupthink, and financial rewards on interest in choosing a career as an internal auditor in sharia organizations. A quantitative approach was employed using a survey method, with data collected through questionnaires administered to 98 undergraduate students. The collected data were analyzed using multiple linear regression to assess the influence of each independent variable on career interest. The results indicate that framing, groupthink, and financial rewards have a positive and significant effect on interest in pursuing a career as a sharia internal auditor. Positive framing of career information enhances students’ perceptions of the profession, while social influence through peer groups strengthens career preferences. In addition, financial rewards remain an important consideration in shaping career decisions. These findings suggest that career interest is influenced not only by individual preferences but also by psychological, social, and economic factors. The study provides practical implications for higher education institutions and sharia organizations in designing career development strategies to increase interest in internal auditing within the sharia sector.